ASSOCIATION OF TWO SUMO3 GENE SINGLE NUCLEOTIDE POLYMORPHISMS WITH CARCASS AND MEAT QUALITY TRAITS OF THE CHINESE SIMMENTAL CATTLE - Li; #; Q. Qin; #; H. Xiao; X. Fang; P. Jiang; Z. Zhao; R. Yang (Journal of Animal and Plant Sciences, 2017)
Small ubiquitin-related modifier 3(SUMO3) is a member of a growing family of ubiquitin-like proteins which is related to post-translational protein modification. Our previous results from gene microarray analysis showed that SUMO3 gene might be associated with carcass and meat quality traits of cattle. In the present study, the association of two novel SNPs, I1-2653A>G and 3’UTR-1120T>C in the intron and 3’UTR region of bovine SUMO3, with 36 traits related to carcass and meat quality was investigated among 375 Chinese Simmental cattle. Statistical analysis demonstrated that the two SNPs were correlated with the carcass and meat quality traits. Individuals with the genotype AA of SUMO3-I1-2653A>G had significantly heavier carcass weight, thicker loin, higher fat coverage and larger eye muscle area (p<0.05). The individuals with genotype TT of SUMO3-3’UTR-1120T>C also showed a significant association with carcass weight, dressing percentage, back fat thickness, fat cover of carcass and rib eye area (p<0.05). SNPs in SUMO3 might be a valuable marker of meat quality traits for marker-assisted selection program in beef cattle breeding and production.
Keywords: SUMO3gene; Mutation; ChineseSimmentalcattle; Meatqualitytrait